Capital Flight from Russia - Loungani, Prakash; Mauro, Paolo (Washington, D.C. : International Monetary Fund, 2000)
This paper documents the scale of capital flight from Russia, compares it with that observed in other countries, and reviews policy options. The evidence from other countries suggests that capital flight can be reversed once reforms take hold. The paper argues that capital flight from Russia can only be curbed through a medium-term reform strategy aimed at improving governance and macroeconomic performance, and strengthening the banking system. Capital controls result in costly distortions and should gradually be phased out as part of that medium-term strategy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet